2021
DOI: 10.3390/ijms22062831
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Opportunities for the Treatment of Squamous Cell Carcinomas: A Focus on Novel Driver Kinases

Abstract: Squamous cell carcinomas of the lung, head and neck, esophagus, and cervix account for more than two million cases of cancer per year worldwide with very few targetable therapies available and minimal clinical improvement in the past three decades. Although these carcinomas are differentiated anatomically, their genetic landscape shares numerous common genetic alterations. Amplification of the third chromosome’s distal portion (3q) is a distinguishing genetic alteration in most of these carcinomas and leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 81 publications
0
11
1
Order By: Relevance
“…Copy number alterations or deletion are ubiquitous in cancer, and are associated with cancer outcomes such as recurrence and death [31]. Although some studies have suggested that copy number or deletion variations correlate with mRNA expression [32], we found that gene ampli cation of m6A family and mRNA expression were not signi cantly associated. However, we found gene alteration in 33.5% of m6A family in the TCGA database.…”
Section: Disscusioncontrasting
confidence: 61%
“…Copy number alterations or deletion are ubiquitous in cancer, and are associated with cancer outcomes such as recurrence and death [31]. Although some studies have suggested that copy number or deletion variations correlate with mRNA expression [32], we found that gene ampli cation of m6A family and mRNA expression were not signi cantly associated. However, we found gene alteration in 33.5% of m6A family in the TCGA database.…”
Section: Disscusioncontrasting
confidence: 61%
“…For example, distal amplification of the long arm of the third chromosome (3q26-29) is highly prevalent in SCC arising in different tissues, including lung, head and neck, and esophageal SCC. The 3q amplicon contains multiple kinase coding genes, such as PIK3CA (phosphatidylinositol 3-kinase catalytic subunit p110alpha), PRKCI [Protein Kinase C (PKC) iota], Mitogen Activated Kinase Kinase Kinase 13 ( MAP3K13) [Leucine Zipper-Bearing Kinase (LZK)], and TNIK (TRAF2- and NCK-interacting kinase) ( Bensen and Brognard, 2021 ). In some instances, a kinase regulatory protein is amplified instead of the kinase coding gene.…”
Section: Protein Kinase Amplification In Cancermentioning
confidence: 99%
“…It has been described in preinvasive and invasive LUSC and represents one of the most striking differences between LUSC and LUAD 5 . Interestingly, 3q amplification is prevalent and carries prognostic relevance in head and neck, cervical, and esophageal squamous cell cancers 6 . The distal amplified area of 3q includes genes that are key in squamous differentiation such as SOX-2, p63, and PIK3CA which explains the prevalence and importance of this genetic alteration in squamous cell carcinomas 6 .…”
Section: Introductionmentioning
confidence: 99%